Calprotectin in the risk stratification of patients with acute dyspnoea in the emergency department - Martin Wollmer; Torgny Wessman; Anders Larsson; Anna C. Nilsson; Olle Melander; Toralph Ruge (Scientific Reports)
Abstract Acute dyspnoea is one of the most common presenting symptoms in the emergency department (ED) and has a variety of underlying causes. Calprotectin is a neutrophil activation marker associated with adverse outcomes in acute cardiovascular and infectious diseases. However, the usefulness of calprotectin in the risk stratification of patients with acute dyspnoea is unknown. The objectives were to, in unselected patients presenting to the ED with acute dyspnoea, investigate the association between (1) calprotectin and 90-day mortality, (2) calprotectin and 90-mortality in subgroups of patients with cardiovascular disease or pneumonia, and (3) calprotectin and illness severity. Single-centre observational cohort study from a university hospital in southern Sweden. A total of 1186 patients from the original Acute Dyspnoea Study, were included. Patients were followed for discharge diagnosis and mortality. Calprotectin concentration was measured in plasma samples collected at the ED. Mean age was 72 years and 56% were women. During follow-up, 143 patients died. In multivariate Cox regression for 90-day mortality, calprotectin in the highest quartile (> 0.96 mg/L) compared to the lowest quartile (< 0.27 mg/L) was associated with a hazard ratio of 2.71 (95% confidence interval 1.39–5.26, p < 0.01). The association with mortality remained significant in the subgroup of patients with acute cardiovascular disease (N = 205, p < 0.01). There was no statistically significant difference in median calprotectin values between survivors and non-survivors with pneumonia (1.62 vs. 1.31, p = 0.155). Multivariate linear regression showed a strong positive correlation between calprotectin and illness severity (respiratory rate ≥ 29 or oxygen saturation ≤ 90%, p < 0.001). In conclusion, calprotectin was associated with 90-day mortality and correlated strongly with illness severity. This indicates that measurement of calprotectin at admission could improve clinical risk stratification of the acute dyspnoeic ED patient. Clinical trial number: Not applicable.